Translating Troilus and Cressida for an iconoclastic socialist production. Issue 1 (July 2019) - Nicolaescu, Madalina
The focus of the article is the investigation of the stage version commissioned for the 1965 production of Troilus and Cressida directed by David Esrig. It looks at the tradition in Romania not to publish translations of Shakespeare produced for the stage before focusing on the differences between the two types of translation (page and stage) in the socialist period. Esrig's production is further discussed as a case study, comparing this version, by Florian Nicolau, with Leon Leviţchi's canonical one, published in 1960.